(untitled) (The Planet, 2022)
Introduction: Nephrotic syndrome is a common renal disease worldwide and an important chronic renal disease in children. Objective: This prospective study is undertaken to assess clinical presentation, associated complications, investigative profile and therapeutic response in children with nephrotic syndrome. Methods and Material: Prospective observational study at pediatric department of our tertiary care hospital. 95 children who were diagnosed to have nephrotic syndrome were included in the study. Cases were noted down into the prestructured proforma with respect to history, examination and investigations. Statistical analysis was done by standard descriptive statistics including Chi-square test and calculating the p value. Results: All patients presented with puffiness of face and swelling of limbs and genital edema in 34.7% & ascites was present in 84.2% of cases, pleural effusion in 17% of cases and HTN in 10.5% of cases. Infections were seen in 33% of cases with UTI being the commonest infection noted (29%). On investigation all patients had hypoalbuminemia in the range of 1.1-2.3 gm. /dl and hypercholesterolemia 202-379mg/dl. Renal function test was normal in all the patients. Microscopic hematuria noted in 9.5 % of cases. Urine protein was 3+ in all cases. Mean urine total protein value was 3.77gm/24 hours and mean protein creatinine was 4.10. Majority of cases (97%) were responders to steroid therapy.